Long pulse D2 and N2 seeded discharges on the upper actively cooled tungsten divertor of WEST. (24th June 2020) - Dittmar, T; Loarer, T; Drenik, A; Bourdelle, C; Brezinsek, S; Desgranges, C; Douai, D; Fedorczak, N; Guirlet, R; Gunn, J; Meyer, O; Laguardia, L; et al.
Abstract: A series of L-mode discharges in upper single null configuration with more than 30 s duration were performed in the WEST tokamak with the strike line on actively cooled tungsten-coated divertor components. This series of discharges accumulated 20 min of plasma and a strike point fluence of ≈ 2 × 10 25 m − 2 in two days of operation in attached conditions. The discharges showed good density control, no tungsten accumulation and overall very benign thermal behaviour of the upper divertor. A subset of the discharges were seeded with nitrogen either in the divertor or midplane region to study plasma–wall interaction and associated ammonia formation in this weakly pumped scenario with all-tungsten plasma-facing components. While ammonia signals remained too weak for useful analysis, a strong dependence of nitrogen plasma penetration efficiency and residence time on the injection location was found. This hints towards a currently underestimated plasma-near nitrogen reservoir in these tokamak discharges in divertor configuration.